Monocyte anisocytosis corresponds with increasing severity of COVID-19 in children - Kane, Abigail S.; Boribong, Brittany P.; Loiselle, Maggie; Chitnis, Anagha P.; Chavez, Hector; Moldawer, Lyle L.; Larson, Shawn D.; Badaki-Makun, Oluwakemi; Irimia, Daniel; Yonker, Lael M. (Frontiers in Pediatrics, 2023)
Introduction Although SARS-CoV-2 infection can lead to severe COVID-19 in children, the role of biomarkers for assessing the risk of progression to severe disease is not well established in the pediatric population. Given the differences in monocyte signatures associated with worsening COVID-19 in adults, we aimed to determine whether monocyte anisocytosis early in the infectious course would correspond with increasing severity of COVID-19 in children. Methods We performed a multicenter retrospective study of 215 children with SARS-CoV-2 infection, Multisystem Inflammatory Syndrome in Children (MIS-C), convalescent COVID-19, and healthy age-matched controls to determine whether monocyte anisocytosis, quantified by monocyte distribution width (MDW) on complete blood count, was associated with increasing severity of COVID-19. We performed exploratory analyses to identify other hematologic parameters in the inflammatory signature of pediatric SARS-CoV-2 infection and determine the most effective combination of markers for assessing COVID-19 severity in children. Results Monocyte anisocytosis increases with COVID-19 severity and need for hospitalization. Although other inflammatory markers such as lymphocyte count, neutrophil/lymphocyte ratio, C-reactive protein, and cytokines correlate with disease severity, these parameters were not as sensitive as MDW for identifying severe disease in children. An MDW threshold of 23 offers a sensitive marker for severe pediatric COVID-19, with improved accuracy when assessed in combination with other hematologic parameters. Conclusion Monocyte anisocytosis corresponds with shifting hematologic profiles and inflammatory markers in children with COVID-19, and MDW serves as a clinically accessible biomarker for severe COVID-19 in children.